Труд и кадры в народном хозяйстве: сборник научных трудов / Свердлов. ин-т нар. хоз-ва - Филиппов Николай Никитич (СИНХ, 1988)
Экземпляры: КХ (20100826) / Инвентарный номер: 943977 / Сис.шифр: 65.9(2)24 / Авт.знак: Т 78 / ГРНТИ: 06.77 / ББК: 65.24